Tobacco dependence treatment in Australia - an untapped opportunity for reducing the smoking burden - Sarah L White; Nikki McCaffrey; Michelle M Scollo (Sax Institute, 2020)
Although the prevalence of smoking has fallen across Australia, population groups with complex psychosocial needs still have higher than average smoking rates. Although most people who smoke want to quit, relatively few report being offered advice and assistance to quit and even fewer use effective smoking cessation supports. Implementing systemic tobacco dependence treatment, as required under Australia's international obligations to the World Health Organization (WHO) Framework Convention on Tobacco Control (FCTC), could further reduce the smoking prevalence, particularly among those experiencing smoking-related health inequalities. Australia's approach to tobacco dependence treatment is characterised herein using Article 14 of the FCTC as a framework.